Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3389/fnbeh.2014.00354
|View full text |Cite
|
Sign up to set email alerts
|

In vitro extinction learning in Hermissenda: involvement of conditioned inhibition molecules

Abstract: Extinction of a conditioned association is typically viewed as the establishment of new learning rather than the erasure of the original memory. However, recent research in the nudibranch, Hermissenda crassicornis (H.c.) demonstrated that extinction training (using repeated light-alone presentations) given 15 min, but not 23 h, after memory acquisition reversed both the cellular correlates of learning (enhanced Type B cell excitability) and the behavioral changes (reduced phototaxis) produced by associative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 90 publications
(155 reference statements)
0
8
0
Order By: Relevance
“…The nudibranch Hermissenda crassicornis exhibits a simple form of associative learning, which has been studied extensively: it can learn to associate light changes with vestibular stimulation (Crow and Alkon 1978). The neural correlates of Hermissenda's associative memories formed during lightmovement pairings have been uncovered (Alkon 1980;Crow and Alkon 1980;Britton and Farley 1999;Tamse et al 2003;Cavallo et al 2014). Hermissenda has also been the subject of investigations related to many other aspects of neuroscience, including sensory and motor neuron physiology (Crow and Tian 2004;Nesse and Clark 2010;Jin and Crow 2011;Crow et al 2013) and the evolution of behaviors and neurotransmitter systems Newcomb et al 2012;Lillvis and Katz 2013).…”
mentioning
confidence: 99%
“…The nudibranch Hermissenda crassicornis exhibits a simple form of associative learning, which has been studied extensively: it can learn to associate light changes with vestibular stimulation (Crow and Alkon 1978). The neural correlates of Hermissenda's associative memories formed during lightmovement pairings have been uncovered (Alkon 1980;Crow and Alkon 1980;Britton and Farley 1999;Tamse et al 2003;Cavallo et al 2014). Hermissenda has also been the subject of investigations related to many other aspects of neuroscience, including sensory and motor neuron physiology (Crow and Tian 2004;Nesse and Clark 2010;Jin and Crow 2011;Crow et al 2013) and the evolution of behaviors and neurotransmitter systems Newcomb et al 2012;Lillvis and Katz 2013).…”
mentioning
confidence: 99%
“…Earlier we found that the defensive reflex conditioning in snails is accompanied by a depolarization shift of the membrane potential and a decrease of the threshold potential (Gainutdinov et al, 1998 ). In recent years there have been a sufficient number of experimental results that demonstrate the membrane correlates of learning (Gillette et al, 1982 ; Alkon, 1984 ; Frysztak and Crow, 1997 ; Cleary et al, 1998 ; Gainutdinova et al, 2003 ; Disterhoft and Oh, 2006 ; Kemenes et al, 2006 ; Nikitin et al, 2006 , 2013 ; Mozzachiodi et al, 2008 ; Jing et al, 2009 ; Debanne and Poo, 2010 ; Gainutdinov et al, 2011 ; Sakharov, 2012 ; Cavallo et al, 2014a , b ). These experiments were done on preparations from trained animals as well as within the cell analogs of learning.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of CaN inhibition seem to be phylogenetically conserved, as the administration of protein phosphatases inhibitors blocked the spike frequency decline observed after an in vitro extinction procedure of classical conditioning in Hermissenda crassicornis ( Cavallo et al, 2014 ).…”
Section: The Molecular Balance: On Calcineurin Kinases and Other Phosphatasesmentioning
confidence: 99%